Elites and Secret Handshakes Versus Metrics and Rule-Based Acclamation: A Comment on “Measuring the Unmeasurable” - Oxley, Leslie (2016)
© 2016, Taylor & Francis Group, LLC. In this issue of Econometric Reviews, Peter Phillips proposes a quantitative (objective) rule that might be used as part of the exercise of measuring merit. In this short comment, I will try and place the need for such a rule (lack of trust and pluralism), potential for adoption (negotiation and power), pros (transparency), and cons (metric failure and loss of institutional memory), within both an historical context and a broader strategic management literature. Ultimately, the adoption of such a rule will depend on its ability to convince the relevant community, via negotiation, that subjective assessments can be appropriately summarized numerically. Rather than argue for objectivity or suggest that numbers are somehow neutral transformations of the real world, it may be advantageous to consider some of the lessons from the critical accounting literature that has focused on the “socially constructed nature” of their numerical systems and techniques.